PENANGANAN TERHADAP PENGEMIS DAN GELANDANGAN UNTUK MEWUJUDKAN KESEJAHTERAAN SOSIAL DAN PENEGAKAN HUKUM DI KOTA SEMARANG - Abdul Kholiq; Sunarto Sunarto (Universitas Suryakancana, 2022)
Beggars and homeless people are classified as a social disease which is a social problem that must be addressed immediately, this is a violation of the law as stipulated in Article 504 of the Criminal Code and Article 505 of the Criminal Code. Efforts to deal with it are usually only like controlling and social rehabilitation who are returned to their place of origin or their family, after being equipped with skills, while the imposition of criminal sanctions by the article mentioned above has not been implemented, because this is also related to Article 34 paragraph 1 of the 1945 Constitution which reads: